Chance health locus of control beliefs in Hindu Nepali patients following anterior cruciate ligament reconstruction relates to perceived sports knee function and symptoms. Issue 20 (25th September 2021) - Nyland, John; Parajuli, Kishor; Singh, Rajesh; Gautam, Arjun; Smith, Austin; Pandey, Chakra
Abstract: Purpose: In western society an internal health locus of control (perception that health outcomes are due to one's own behavior) is related to perceived sports knee function following anterior cruciate ligament reconstruction. This prospective cohort study was performed to determine if similar health beliefs exist among athletically active Hindu patients from Nepal following primary anterior cruciate ligament reconstruction. Materials and methods: Twenty-five consecutive patients (21 men, 4 women) of 26.7 ± 7.7 years of age participated in this study at 4.2 ± 2 months post-surgery. All subjects had undergone primary anterior cruciate ligament reconstruction using a bone-patellar tendon-bone autograft, with anteromedial portal use for femoral tunnel drilling and interference screw fixation. Subjects completed the Knee Outcome Survey – Sports Activities Scale symptoms and functional limitations during sports subscales and Form C of the Multidimensional Health Locus of Control scales. Descriptive and correlational statistical analysis was performed. An alpha level of p < 0.05 was selected to indicate statistical significance. Results: Knee Outcome Survey – Sports Activity Scale symptoms scores were 71.3 ± 18 (range = 43–97) and functional limitations scores were 42.4 ± 34 (range = 10–95). Multidimensional Health Locus of Control subscale scores were Internal (27.8 ± 4.6), Chance (21.5 ± 6.3), Doctors (16.1 ± 1.9) and other people (14 ± 3.5). Significant relationships were not observed between symptoms or functional limitations subscale scores and Multidimensional Health Locus of Control internal, doctors or powerful others subscale scores. However, strong ( r = 0.72) and moderately strong ( r = 0.48) relationships were observed between the Multidimensional Health Locus of Control chance subscale score and Knee Outcome Survey – Sports Activities Scale functional limitations and symptoms subscales, respectively. Conclusion: Following primary anterior cruciate ligament reconstruction, Hindu patients from Nepal displayed strong relationships between perceived knee function and symptoms and the Multidimensional Health Locus of Control chance subscale. Identification and targeting the beliefs of patients may be clinically important to facilitating positive treatment progression and behavioral changes during post-surgical rehabilitation programs. Further studies are needed to determine how medical and rehabilitation clinicians who provide care to patients from eastern, collectivist cultures can optimize healthcare strategies for patients with sociocultural or religious/spirituality influences that possess strong chance or luck beliefs. Implications for Rehabilitation: Following primary anterior cruciate ligament reconstruction, Hindu patients from Nepal displayed strong relationships between perceived knee function and chance health locus of control beliefs. Identification and targeting the health locus of control beliefs of patients may be clinically important to facilitating positive treatment progression and behavioral changes during post-surgical rehabilitation programs. Medical and rehabilitation professionals need to become more aware of how a patient's religious or spiritual beliefs may conflict with healthcare instructions, or, alternatively, could be better harnessed to facilitate improved program adherence.